Յուրի Վեսելովսկին և հայ իրականությունը - Զաքարյան, Անուշավան (ՀՀ ԳԱԱ «Գիտություն» հրատ.)
Исполнилось 150 лет со дня рождения известного русского ученого-литературоведа, поэта, переводчика, арменоведа, первого в России, с конца 80-х годов XIX века, глубокого исследователя и пропагандиста истории, литературы, искусства армянского народа – Юрия Алексеевича Веселовского. Его исследования являются ценным вкладом в деле развития арменоведения в России. This year marks the 150th anniversary of the birth of the famous Russian scientist-literary scholar, poet, translator, Armenologist, Yuri Aleksey Veselovsky – the first thorough researcher and propagandist of the history, literature and art of the Armenian people in Russia since the late 80s of the 19th century. His studies are a valuable contribution to the development of Armenology in Russia.
Keywords: Գրականագիտություն